2009
DOI: 10.1002/art.24616
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the osteoarthritis susceptibility–associated GDF5 regulatory polymorphism

Abstract: Objective. Single-nucleotide polymorphism (SNP) rs143383 (T to C) in the 5 -untranslated region (5 -UTR) of GDF5 has recently been reported to be associated with osteoarthritis (OA) susceptibility, with lower expression of the risk-associated T allele observed in vitro and in vivo. The in vivo studies were performed on cartilage tissue from OA patients. The present study was undertaken to expand the analysis of the effect of this SNP on GDF5 allelic expression to more joint tissue types, to investigate for cis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 23 publications
8
94
0
2
Order By: Relevance
“…Previous studies have found that a function of SNP in GDF5 is associated with susceptibility to osteoarthritis at different joint locations and to lumbar disc degeneration. 6,16,24 In the present study, the T allele as a predisposing allele was more common in the case group individuals than in the control group individuals. The polymorphism of GDF5 may have an impact on the development of bone, cartilage, and soft tissue in the low-back area through exerting allelic differences on transcriptional activity.…”
Section: Discussionsupporting
confidence: 40%
“…Previous studies have found that a function of SNP in GDF5 is associated with susceptibility to osteoarthritis at different joint locations and to lumbar disc degeneration. 6,16,24 In the present study, the T allele as a predisposing allele was more common in the case group individuals than in the control group individuals. The polymorphism of GDF5 may have an impact on the development of bone, cartilage, and soft tissue in the low-back area through exerting allelic differences on transcriptional activity.…”
Section: Discussionsupporting
confidence: 40%
“…This association was confirmed in a large-scale meta-analysis; however, the magnitude of effect was less than previously reported (Evangelou et al, 2009). Interestingly, Egli et al found that GDF5 expression imbalance was not limited to articular cartilage, but found in multiple joint tissues analyzed (synovium, fat pad, meniscus, ligaments) (Egli et al, 2009). …”
Section: Other Factors That May Regulate Chondrocyte Differentiation mentioning
confidence: 57%
“…28 The most associated SNP (rs143383) is a functional variant, and the susceptibility allele shows decreased GDF5 transcription in vitro and in vivo. [28][29][30] The same allele was reported to be associated with adult height in Caucasians through a GWAS using subjects with non-insulin-dependent diabetes mellitus. 31 Valdes et al 32 assessed rs143383 for OA in the UK Caucasians using 999 knee OA, 843 hip OA and 1166 control samples, and they replicated the association of GDF5 in knee OA (OR¼1.29, 95% CI of 1.14-1.47; P¼8Â10 À5 ).…”
Section: Gdf5mentioning
confidence: 80%